A Phase I Study of Ganetespib and Ziv‐Aflibercept in Patients with Advanced Carcinomas and Sarcomas. (4th June 2018) - Meehan, Robert; Kummar, Shivaani; Do, Khanh; O'Sullivan Coyne, Geraldine; Juwara, Lamin; Zlott, Jennifer; Rubinstein, Larry; Doroshow, James H.; Chen, Alice P.
Abstract: Lessons Learned: The combination of the antiangiogenic agent ziv‐aflibercept and the heat shock protein 90 inhibitor ganetespib was associated with several serious and unexpected adverse events and was not tolerable on the dosing schedule tested. Studies such as these emphasize the importance of considering overlapping toxicities when designing novel treatment combination regimens. Background: Although inhibition of angiogenesis is an effective strategy for cancer treatment, acquired resistance to antiangiogenic therapy is common. Heat shock protein 90 (Hsp90) is a molecular chaperone that regulates various oncogenic signaling pathways involved in acquired resistance and has been shown to play a role in angiogenesis. Combining an antiangiogenic agent with an Hsp90 inhibitor has therefore been proposed as a strategy for preventing resistance and improving antitumor activity. We conducted a single‐arm phase I study evaluating the combination of ziv‐aflibercept, an antiangiogenic drug, with the Hsp90 inhibitor ganetespib. Methods: Adult patients were eligible if they had recurrent or metastatic gastrointestinal carcinomas, nonsquamous non‐small cell lung carcinomas, urothelial carcinomas, or sarcomas that had progressed after at least one line of standard therapy. Ziv‐aflibercept was administered intravenously on days 1 and 15, and ganetespib was administered intravenously on days 1, 8, and 15, of each 28‐day cycle. Results: Five patients were treated with the combination. Although three patients achieved stable disease, study treatment was associated with several serious and unexpected adverse events. Conclusion: The dose escalation phase of this study was not completed, but the limited data obtained suggest that this combination may be too toxic when administered on this dosing schedule.